CHARACTERISTICS OF IMAGE CREATION IN A.ABDIEV’S WORK "EAGLE’S PEAK" - Ktaybekova, Zulfiya Kengesbaevna (SCIENCE and SOCIETY, 2026)
In the short story "Eagle Peak" by the Karakalpak writer A. Abdiev, the features of image creation are artistically analyzed. In the work, the writer examines the issue of human fate, the law of nature, honesty and honor through the life of the eagle. The struggle for survival in nature, the relationship between the strong and the weak, is interpreted through examples of the eagle, argali, crow and other characters in the work.